The effects of interactive health education on compliance of mothers to postpartum care - Tiburan, Nilo C. (1997)
Health education is viewed as an important tool to achieve today's health care agenda--promotive and preventive health care. Its use in nursing practice is aimed to provide the clients with basic health facts and skills and assists them with their disabilities and/or for them to achieve higher level of wellness. The effective implementation of health education is an essential nursing responsibility to increase, if not to assure client compliance with the prescribed health regimen. In the process of imparting health education, the nurse should see to it that interaction takes place for it to become more effective. Nurse's power in interactions with patients is capable of effecting change (Hervison, 1995). It is through the interaction that the nurse reaches out the patient and do something that may lead to behavioral change. On this premise, health education should provide unlimited opportunities to interact with clients. Hence, the main concern of this study was to determine the effects of Interactive Health Education on client compliance.This study further sought answers to the following questions:1. Is there a significant relationship between client comliance and the following factors: a. education; b. age; c. type of work.2. To what extent are the client compliance and satisfaction with health education given related?The post test only control group design (a quasi-experimental design) was the research design of choice which utilized tools like questionnaire and interview-schedule devised for the study. To achieve constancy of condition in quasi-experiment, the study was conducted at Jose R. Reyes Memorial Medical Center and included uncomplicated primiparas who met the inclusion criteria as subjects. A total of eighty (80) mothers were taken and assigned equally to control and experimental groups through simple random sampling. Respondents who were in control group received the structured health education (the usual practice of the hospital), and respondents in experimental group received the interactive health education. Compliance with health education was assessed at the Out Patient Department Clinics one week after the clients were discharged from the hospital. Sixty-seven (67) respondents were able to complete the study, 32 of them were from control group and 35 were from experimental group. Comparability of two groups was checked through chi-square statistic of homogeneity.Data were analyzed using descriptive statistics, t-test, ANOVA, Pearson product moment correlation, and chi-square statistic.
The study unveiled the following findings:1. Interactive health education has positive effects on the compliance of mothers to postpartum care. Respondents who received the interactive health education have significantly higher compliance scores than those who received the structured health education.2. Difference of means of compliance scores of clients in control and experimental group was 8.439. T-test showed a significant difference in the means of compliance scores of respondents of both groups at p=.000022.3. There is a significant relationship between compliance and type of work (X2=10.75, p=0.0046). Respondents who had worked outside of their homes tend to have lower compliance scores than those who are home-based.4. Client satisfaction with health education given had positive high correlation with compliance (r=+.92) which is significant at p=.0001. High values of satisfaction are associated with high values of compliance.5. Age and education had no significant relationship with compliance.As a whole, the results of the study showed empirical evidence of the positive effects of interactive health education on compliance of mothers to postpartum care. Conversely, health education should be made as an opportunity to interact with clients and create a motivating climate for learning. Hence, recommendations of this study are directed towards identifying avenues to increase interaction with clients, molding nurses to become effective facilitators of learning, and identifying support system for this endeavor.
Thesis (Master of Arts in Nursing)--University of the Philippines Manila.
Keywords: Health education; Health education -- Parent participation; Patient education; Post partum care